Pengaruh komunikasi dan disiplin kerja terhadap produktivitas kerja karyawan PT. Agrindo Maju Lestari di Kabupaten Tangerang - Melly Hernawati; Aries Setiawan; Dede Saparudin; Merrisa Fermica Iskandar (Universitas Tangerang Raya, 2023)
This study aims to analyse the effect of communication and work discipline on employee productivity of PT Agrindo Maju Lestari in Tangerang Regency. method in this study uses quantitative methods. Sampling technique using Random Sampling. The number of samples used in this study was 110 employees of PT Agrindo Maju Lestari in Tangerang Regency. The data collection method used is using a questionnaire.The results of this study indicate that communication has an effect on employees of PT Agrindo Maju Lestari in Tangerang. This is because the Communication variable has a t value of 3.908 greater than the t table of 1.982 and a significance value of 0.000 less than 0.05. Work Discipline affects employees of PT Agrindo Maju Lestari in Tangerang Regency. This is because the Work Discipline variable has a t value of 13.677 greater than the t table of 1.982 and a significance value of 0.000 smaller than 0.05. Communication and work disine affect the employees of PT Agrindo Maju Lestari in Tangerang Regency. This is because the Communication variable has a calculated F value of 162.973 greater than the f table of 3.08 and a significance value of 0.000 smaller than 0.05. The magnitude of the effect of communication and work discipline on employees of PT Agrindo Maju Lestari in Tangerang Regency is 75.3%, which means that the contribution of employee work productivity can be explained by the independent variables, namely communication and work discipline. Then the remaining 24.7% is explained by other variables not examined in this study.